Religious Education Practices in Pesantren: Charismatic Kyai Leadership in Academic and Social Activities - Naufal Ahmad Rijalul Alam (UIN Sunan Ampel Surabaya, 2020)
This study investigates religious education practices through Kyai leadership characteristics as the caregiver as well as a decision-maker in pesantren. qualitative data are gathered through documentation, observation, and interview at Pesantren Bina Insani, Yogyakarta. The education at Pesantren Bina Insani has been well known as community-based education, derived from the aspirations of the community, and to meet their interests. As a community-based educational institution, the Pesantren is very dependent upon the initiative and charisma of the Kyai as the leader. The results demonstrate that Kyai Teguh’s charismatic leadership characteristics have turned into unwritten standards for people under his influence in managing the Pesantren and developing their social skills. From leadership theory perspective, Kyai Teguh’s characteristics are the rational grounds for his followers in terms of decision making, wok-ethics, and social interactions.